Analysis of Smartphone Usage and Changes in Social Cohesion Patterns - Rosmini Rosmini; Muamar Asykur; Muhammad Basir (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to analyze smartphone usage and changes in students' social cohesion patterns at UPT SDI Barugaia No. 60, Selayar Islands. The focus of the study includes students' smartphone usage patterns, social cohesion patterns formed in their social lives, and changes in togetherness and social solidarity that emerge as a result of the use of digital devices. This study uses a qualitative approach with ethnomethodology studies. The research informants consisted of students as the main informants and teachers as key informants. Data collection techniques were carried out through observation, in-depth interviews, and documentation, while data analysis was carried out through data reduction, data presentation, and drawing conclusions. The results show that students' smartphone use occurs collectively through online gaming activities, WhatsApp group communication, and sharing digital content that forms a new social interaction space outside the school environment. Students' social cohesion patterns are still formed through academic cooperation and friendships, but develop stronger in small groups based on shared digital experiences. In addition, students' togetherness and social solidarity have changed from physical game activities to solidarity based on digital communication networks through the practice of sharing hotspots, assignment information, and cooperation in online gaming activities. Thus, smartphone use does not weaken students' social cohesion, but transforms the form of togetherness and solidarity in the social relations structure of peer groups.